Calcium sulfate bone cements with nanoscaled silk fibroin as inducer. Issue 8 (6th March 2019) - Xu, Rui; Lian, Xiaojie; Shen, Yiling; Zhang, Yue; Niu, Baolong; Zhang, Siruo; Guo, Qi; Zhang, Quanyou; Du, Jingjing; Li, Fen; Lu, Qiang; Huang, Di; et al.
Abstract: Both nanostructures and conformations of different protein/polysaccharide additives have critical influence on the performance of calcium sulfate (CS) bone cements. Silk fibroin (SF) as matrix and additives has been introduced to develop bone scaffolds and cements. Here, β‐sheet‐rich SF nanofibers (SFF) was used to tune the solidification of CS, achieving better mechanical and biological properties. The ratio of SFF was adjusted to further optimize CS functions. Compared to that regulated with natural silk fibers (NSF) and SF solutions (SFS), the SFF‐induced CS showed smaller size and more filament structures. Better mechanical properties were achieved, suggesting the superiority of the SFF as the solidifying solution to combine with α‐calcium sulfate hemihydrate (α‐CSH) at the same liquid/solid (L/S) ratio. Scanning electron microscope, X‐ray diffraction, Fourier transform infrared spectroscopy, setting time, porosity, mechanical performance test, degradation performance test, and water resistance test were used to demonstrate the properties of this bone repair cement. Cell culture experiments in vitro was used to evaluate the biocompatibility of this composited material. In conclusion, the results demonstrated that nanofibers was a better form of SF in the modification of CSH cement. And the research conducted in this article on improving the mechanical and biological properties of CSH would supported the reference for later clinical experiments. © 2019 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B:2611–2619, 2019.